La educación desde la perspectiva de Tomás de Aquino en el contexto de la cibercultura (2020)
This article offers a reflection on education in the 21st century, from the perspective of Thomas Aquinas. Thus, it promotes an updating of the decisive issues of pedagogical practice from a realistic, human and ethical perspective, based on Thomas Aquinas' educational and pedagogical ideology, in the context of cyberculture. To this end, the anthropological, epistemological and axiological implications of Thomas Aquinas' thought are presented, with the purpose of applying them to educational practice based on pedagogical realism. With this objective, we have chosen to make a qualitative design of hermeneutic nature, in which the texts of Saint Thomas are triangulated with the classic texts of cyberculture and cybercultural convergence. Based on this, some lines of action are proposed to stimulate the reflection of the curricular design, according to the concepts of person, truth and virtue, distinctive of Saint Thomas, widely emerging in the so-called digital society.